Analisis Perilaku Pencegahan Stunting Pada Ibu Balita Di Kecamatan Uluere Kabupaten Bantaeng - Nurmisbahullah; Muhammad Ikhtiar; Nurul Ulfah Muttalib (Window of Public Health Journal, 2025)
Nutritional problems in toddlers, such as stunting, wasting, and underweight, remain a global concern. This study, employing a quantitative research type with a cross-sectional design, is significant in its aim to establish the relationship between variables by analyzing the data collected. The population for this study is 150 mothers with toddlers in Uluere District, Bantaeng Regency. The sample used in this study is based on the Slovin Formula of mothers who have toddlers in Uluere District, Bantaeng Regency. The study's results, following the Chi-Square Test, revealed a significant relationship between the attitudes of mothers of toddlers and stunting prevention measures, with a p-value of 0.000 <0.05. The conclusion of this study underscores the importance of mothers' attitudes in stunting prevention measures in Uluere District, Bantaeng Regency.